New resistorless current-mode quadrature oscillators using 2 CCCDTAs and grounded capacitors - Sakul, Chaiwat; Jaikla, Winai; Dejhan, Kobchai (My University, 2011)
The current-mode quadrature oscillators using 2 current controlled current differencing transconductance amplifiers (CCCDTAs) and 2 grounded capacitors are presented. The proposed oscillators can provide 2 sinusoidal output currents with 90° phase difference. The oscillation condition and oscillation frequency can be electronically/independently controlled by adjusting the bias current of the CCCDTA. High output impedances of the configuration enable the circuit to drive the external load without additional current buffers. The use of only grounded capacitors is ideal for integration. The PSpice simulation results are depicted. The given results agree well with the theoretical anticipation.
Keywords: CCCDTA; Current-mode; Sinusoidal oscillator